# 5x-3y=2(x-y)

## Simple and best practice solution for 5x-3y=2(x-y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 5x-3y=2(x-y) equation:

Simplifying
5x + -3y = 2(x + -1y)
5x + -3y = (x * 2 + -1y * 2)
5x + -3y = (2x + -2y)
Solving
5x + -3y = 2x + -2y
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2x' to each side of the equation.
5x + -2x + -3y = 2x + -2x + -2y
Combine like terms: 5x + -2x = 3x
3x + -3y = 2x + -2x + -2y
Combine like terms: 2x + -2x = 0
3x + -3y = 0 + -2y
3x + -3y = -2y
Add '3y' to each side of the equation.
3x + -3y + 3y = -2y + 3y
Combine like terms: -3y + 3y = 0
3x + 0 = -2y + 3y
3x = -2y + 3y
Combine like terms: -2y + 3y = 1y
3x = 1y
Divide each side by '3'.
x = 0.3333333333y
Simplifying
x = 0.3333333333y`